FAKTOR DOMINAN PENYEBAB KEJADIAN KEKURANGAN ENERGI KRONIK PADA IBU HAMIL - Firda Fibrila; Herlina Herlina; M Ridwan; Addi Mardi Harnanto (Jurnal Medikes (Media Informasi Kesehatan), 2022)
CED during pregnancy triggers cases of hypertension pregnancy, pre-eclampsia, bleeding, and premature rupture of membranes and causes fetal growth retardation during pregnancy. Many factors cause KEK. Therefore cases of KEK need to be considered so that they can be managed properly before and during pregnancy. Objective: to obtain the dominant factor causing SEZ in pregnant women. Methods: This research is an observational analytic study with an explanative quantitative method, using a case-control design. The sample in this study was divided into two groups, namely the case group of 36 pregnant women and the control group of 73 pregnant women. The research was conducted at the Independent Midwife Practice in Jatidatar, Central Lampung. Bivariate analysis using chi-square test. Multivariate analysis using multiple logistic regression test. The significance level was set at 95%. Results: Of the 6 variables that were tested by bivariate, only 3 variables were associated with the incidence of SEZ. Age (ρ=0.750), education (ρ=0.541), and occupation (ρ=0.132) were concluded to be unrelated to the incidence of SEZ, where each of these variables -value >0.05. Variables related to the incidence of SEZ in the statistical test results, namely; income (ρ=0.001, 95% CI: 1.911–13.821, OR = 5.139), parity (ρ=0.037, 95% CI: 1.137–5.903, OR = 2.591), anemia (ρ=0.001, 95% CI: 2.354– 13,454, OR = 5,628). In the final modeling, anemia was the dominant variable (POR/Exp(B) = 4.312, 95% CI = 1.741 – 10.683). Conclusion: Family income, maternal parity, and anemia are factors that play a role in triggering SEZ in pregnant women. Anemia after being controlled by the family income variable became the dominant factor causing KEK in pregnant women.